Analisis Arah dan Kecepatan serta Besar Persentase Fase Angin Menggunakan WRPLOT Tahun 2015-2020 di Stasiun Klimatologi Kelas II Paniki Atas Minahasa Utara - Keintjem, Regina Gabriel; Baskoro, Winardi Tjahyo; Buana, Muhammad Candra; Nurmalasari, Nurmalasari; Trisnawati, Ni Luh Putu; Ratini, Ni Nyoman (Universitas Hamzanwadi, 2023)
Weather and climate deviations have resulted in extreme weather in most parts of Indonesia which has triggered a number of natural disasters, such as tornadoes and floods that have occurred in various areas. It is necessary to know this in order to prevent something undesirable from happening. This writing aims to understand wind direction and speed and determine the percent of wind phases using WRPLOT V7.0 from 2015 to 2020. WRPLOT (Wind Rose Plots for Meteorological Data) is a windrose program for meteorological data. This software provides windrose diagram displays, frequency analysis and diagrams for several meteorological data formats. The data taken is wind data with the highest direction and highest speed recorded by the Class II Paniki Atas North Minahasa Climatology Station. Wind direction and speed data from 2015 to 2020 using WRPLOT obtained wind rose and wind speed graphs, namely 7 (from the dominant direction West), 2 (from the dominant direction Southeast), 2 (from the dominant direction South), and 1 (from the dominant direction Northeast), and the percentage of winds blowing from 2015 to 2020 at speeds ≥22 knots, namely more than 60%. Where the percentage of speeds ≥22 knots is highest in September and October with a percentage of 86%, while the percentage of speeds ≥22 knots is lowest in June with a presentation of 68.3%.